(NrADIACIONNO(B-(NSTIMULIROWANNYE PROCESSY W [IROKO]ELEWYH MATERIALAH (B:s (NsBORNIK NAU^NYH TRUDOW (B/s - (NwALBIS(B, (Nq(B.s; (Nnii FIZIKI TWERDOGO TELA (B((NrIGA(B)s; (NlATWIJSKIJ GOSUDARSTWENYJ UNIWERSITETs ((NrIGA (B:s (Nlgu(B,s, 1987)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NkRISTALLY (B- (NdEJSTWIE IONIZIRU@]IH IZLU^ENIJ (B- (NsBORNIKIs